Bird species of Hutan Kota BNI Banda Aceh, Indonesia - Aida Fithri (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Hutan kota BNI is one of Kota Banda Aceh City Park. It takes place in Tibang village Syiah Kuala district, Banda Aceh, Indonesia. It used to be fishpond with mangrove trees planted inside the fish pond. After tsunami all mangrove trees were destroyed and this area have become terrestrial zone. Since 2010 many plants were replantedand attracted many birds to came to this area. Data collection by using transect method was performed since January until June 2012. In this study 26 bird species (14 families) were found within this area. Some of birds are migratory and protected birds